2020
DOI: 10.1111/ans.15708
|View full text |Cite
|
Sign up to set email alerts
|

Health costs of post‐operative complications following rectal resection: a systematic review

Abstract: BackgroundPost‐operative complications following rectal resection pose significant health and cost implications for patients and health providers. The objective of this study is to review the associated cost of complications following rectal resection. This included reporting on the proportion and severity of these complications, associated length of stay and surgical technique used. Studies were sourced from Embase OVID, MEDLINE OVID (ALL) and Cochrane Library databases by utilizing a search strategy.MethodsT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…There is a higher risk of medical and surgical postoperative complications, especially severe ones, in this subgroup of patients than in the general population [ 21 28 ]. The incidence of these complications ranges from 6% [ 29 , 30 ] to over 65% [ 29 , 31 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…There is a higher risk of medical and surgical postoperative complications, especially severe ones, in this subgroup of patients than in the general population [ 21 28 ]. The incidence of these complications ranges from 6% [ 29 , 30 ] to over 65% [ 29 , 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…C. Frail elderly patients who underwent colorectal resection for cancer have a more prolonged hospital stay [ 21 , 22 ], which ranges from 5 days [ 29 , 32 ] to more than 20 days [ 29 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A similar New Zealand study also found a doubling of costs with complications, but a less marked association with complication severity [ 38 ]. Systematic reviews for liver and rectal surgery also support this relationship between cost and complications, and cost and complication severity, but considerable study heterogeneity, and presumably the contextual nature of cost, limits the financial conclusions which can been drawn [ 39 , 40 ].…”
Section: The Measured Costs Of Complicationsmentioning
confidence: 99%